Merapi’s Lahar Benefit at Putih River, Magelang - Ahmad Syukron Prasaja (USN Kolaka, 2019)
Damage to settlements and agricultural land due to lahar in 2011 still leaves a mark that cannot be forgotten. The lahar disaster was caused by the collapse of the material from the eruption of Merapi Volcano which had accumulated in the upstream due to rainfalls having an average intensity of about 40 mm in 2 hours that occurs at rainy season from November to April. Putih River is one of river that effected by lahar disaster. This research wants to know community income before and after lahar disaster and usefulness of lahar material for community that affected by lahar disaster. The method to reach the aim are structure and in-depth interviews with people that effected by lahar disaster. The result is most of community that effected by lahar disaster has income increase by Rp12,500 until Rp100,000 per-day and the community can use the material lahar that deposit around Putih River by selling it as building material, and then they can build a building according Contractor, BPS, and Community standard.